2004
DOI: 10.3748/wjg.v10.i19.2878
|View full text |Cite
|
Sign up to set email alerts
|

Expression of plasma vascular endothelial growth factor in patients with hepatocellular carcinoma and effect of transcatheter arterial chemoembolization therapy on plasma vascular endothelial growth factor level

Abstract: A high pre-treatment P-VEGF level is a useful marker for tumor progression, especially for vascular invasion. TACE increases the level of P-VEGF only temporarily which may be associated with tumor ischemia. P-VEGF may be useful in predicting treatment response, monitoring disease course after TACE and judging the effect of different TACE regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
204
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(216 citation statements)
references
References 32 publications
7
204
1
Order By: Relevance
“…37 The stimulated angiogenesis is possibly due to hypoxia induced by TAE, as it has been demonstrated that expression of HIF-1a and its subsequent VEGF could be upregulated by ligation of hepatic artery, 38 a similar hypoxia-inducing procedure to TAE. However, in one report by Li et al, 39 transurethral chemoembolization (TACE) had little influence on tumor angiogenesis, possibly due to the application of chemotherapeutic drugs, which have been shown to inhibit the tumor angiogenesis. 40 Potential advantages of AAV mediated antiangiogenic gene therapy are the sustained expression of the antiangiogenic factors and highly-localized delivery.…”
Section: Discussionmentioning
confidence: 99%
“…37 The stimulated angiogenesis is possibly due to hypoxia induced by TAE, as it has been demonstrated that expression of HIF-1a and its subsequent VEGF could be upregulated by ligation of hepatic artery, 38 a similar hypoxia-inducing procedure to TAE. However, in one report by Li et al, 39 transurethral chemoembolization (TACE) had little influence on tumor angiogenesis, possibly due to the application of chemotherapeutic drugs, which have been shown to inhibit the tumor angiogenesis. 40 Potential advantages of AAV mediated antiangiogenic gene therapy are the sustained expression of the antiangiogenic factors and highly-localized delivery.…”
Section: Discussionmentioning
confidence: 99%
“…This is attributable to the fact that most VEGF in the peripheral circulation is carried in the platelets, and the VEGF is released when the platelets are activated during blood clotting. It has been postulated that platelets may serve as a scavenger or storage of VEGF from the tumor, and the release of VEGF from the platelets at distant metastasis may play a central role in the process of hematogenous dissemination of cancers [30] . A study has demonstrated that increased levels of bone marrow-derived endothelial progenitor cells in the peripheral circulation of patients with advanced HCC, and a high correlation between serum VEGF levels and levels of circulating endothelial progenitor cells were observed [31] .…”
Section: Discussionmentioning
confidence: 99%
“…The drug should be present long enough to cover the early proliferative response to the ischemic effect after the embolization procedure, which is known to peak at day 1 and then gradually decrease (35). In comparison, the Sutent® monography (34) reported a t max between 6 and 12 h after capsule (sunitinib malate) intake and Speed et al (36) determined an elimination half time of 51 h in humans after an oral dose of 50 mg.…”
Section: Chow Et Al (18) Stated 20 To 40 Mg/kg Po As a Minimal Daimentioning
confidence: 99%